"Sheep Eat Men": A Retrospective Proverb. (December 2014) - Doyle, Charles Clay
Abstract : The expression "Sheep are eating men" or "Sheep devour men" looks back to Utopia for its origin. However, no such concise expression actually occurs there. In recent decades the expression has frequently been quoted without awareness of the literary connection, assumed to have been proverbial in medieval or early modern times. Perhaps, in a strange way, it has become proverbial in our own time, although most often when it is uttered nowadays, it will be explicitly associated with the distant past.